Identifying and providing museum services for ubiquitous visitors. (17th December 2021) - Khanwalkar, Preeti; Venkataram, Pallapa
Recent technological advancements have enabled personalised services for the museum ubiquitous visitors. Museum ubiquitous visitors are the visitors who are free to access required services anywhere, any time through any possible devices without making explicit requests. In this work, we propose the system of identifying and providing museum services to cater to the individual requirements of the ubiquitous visitors. The system is designed to provide exhibit information museum services to the ubiquitous visitors. The proposed system employs the ubiquitous visitor model and automatically identifies the required exhibit information URL for the ubiquitous visitors. Further, from the identified URL, based upon the dynamic requirements of the ubiquitous visitors, the system provides tailored exhibit information to the visitors. The simulation results show that the proposed system, using the ubiquitous visitor model, significantly reduces the time to identify and provide required exhibit information museum services for the ubiquitous visitors.